EDUCATION AND ART – SEARCH FOR FREEDOM. A STUDY OF THE CLASS BY EDUCATOR JOEL MARTINS. THE DISTANCE OF BRAZILIAN SCHOOLS - Lima, Luiz Augusto Normanha (Seven Editora, 2025)
This article is a transcription of a lecture entitled Education – Art and the search for freedom, by Professor Joel Martins in April 1990, in which this renowned Brazilian philosopher generously offered during his classes at the Pontifical Catholic University, at PUC São Paulo, with a mastery of knowledge baggage. It is, therefore, a tribute to 35 years of this text written by Master Joel Martins. He begins by showing that freedom is a dialectical issue as something incomplete that needs to be completed in overcoming the obstacles we face. points out the difference between freedom and behavior free of responsibility, authority and obligations. To be free is to be autonomous, to have choices in the face of a conditioned world. Freedom encompasses overcoming obstacles, for possible choices of activities – absence of obstructions on the road, on which man decides to walk. Although freedom is so desired, it is so important to be free, it also leaves an existential void for being assumed as a guarantee, as having its own existence. And that even though freedom is linked to prosperity, overcoming obstacles, limitations, getting out of poverty, even so, many people do not want to risk being free, because it is scary to be considered, in society, as different. In short, freedom is knowing how to inhabit the rules of duty and power and this leads us to a power of imagination and a duty to alert to its use. DOI: https://doi.org/10.56238/sevened2025.018-006